Evaluation of solubility, disintegration, and dimensional alterations of a glass ionomer root canal sealer - Carvalho-Júnior Jacy Ribeiro; Guimarães Luiz Fernando L.; Correr-Sobrinho Lourenço; Pécora Jesus D.; Sousa-Neto Manoel D. (Fundação Odontológica de Ribeirão Preto, 2003)
The aim of this study was to evaluate the glass ionomer cement Ketac-Endo (K) compared with Endofill (E), N-Rickert (N), and Sealer 26 (S) in terms of disintegration, solubility, and dimensional alteration properties, based on ADA Specification No 57. For dimensional alterations, 12-mm high cylindric specimens measuring 6 mm in diameter were prepared and left to stand for a period corresponding to three times the setting time. These specimens were immersed in 30 ml of deionized distilled water after measuring their length with a caliper. Thirty days later, the sample was removed from the container, dried and measured again for length to determine the percent of dimensional alteration. For solubility and disintegration, 1.5-mm thick cement samples measuring 20 mm in diameter were prepared and left to stand for a period corresponding to three times the setting time. The samples were weighed and immersed in 50 ml of deionized distilled water. After seven days, the samples were removed, dried and weighed again to determine the mass loss of each sample, expressed as percentage of original mass. This was considered to correspond to solubility and disintegration of cement. The results were: dimensional alteration: E (+0.14), K (-0.24), N (+0.23), S (+3.26); for disintegration and solubility: E (3.90), K (9.90), N (3.00), S (0.25). We concluded that the dimensional alteration of all cements conformed to ADA standards; Endofill and Ketac-Endo sealers presented higher values for disintegration and solubility than ADA recommendations. Obturating a root canal with a sealer that presents low disintegration and low contraction could minimize the penetration of fluids into the root canal system, thus sealing the space hermetically.